Editorial [ Hematopoietic Stem Cell Transplantation and Graft-Versus-Host Disease (Guest Editor: T. Iwasaki)] - Iwasaki, Tsuyoshi (Current Medicinal Chemistry - Immunology, Endocrine & Metabolic Agents, 2005)
Graft-versus-host disease (GVHD) is a devastating complication of allogeneic hematopoietic stem cell transplantation (HSCT). Although significant progress in the treatment of GVHD has been made, several obstacles remain in overcoming this complication. Animal models have been critical to our understanding of the pathophysiology of GVHD, and multiple clinical approaches have been taken, based on experimental animal models. This volume brings together contributions from experts in the fields of HSCT and GVHD research, reviewing GVHD pathophysiology and GVHD therapy. Ferrara et al. review the pathophysiology of acute GVHD, considering this disorder as a three-step process in which the innate and adaptive immune systems interact. Ikehara reviews a new HSCT method, intra-bone marrow transplantation, by which GVHD is prevented even when donor lymphocyte infusion is carried out. Fowler and Gress review the role of sirolimus in allogeneic HSCT, and they describe a new adoptive Th2 cell therapy using sirolimus. Iwasaki reviews novel therapies aimed at protecting against GVHD by using protective growth factors, focusing on hepatocyte growth factor and sphingosine-1-phosphate. Via et al. review the parent-into-F1 model of GVHD that is useful for studying immune responses in non-myeloablative conditioning regimens, chronic GVHD, and autoimmunity. Finally, Levy reviews approaches to regulate experimental as well as clinical GVHD during three different stages, including the use of CD4+CD25+ regulatory T cells. We gratefully acknowledge the generous efforts of all of these contributors. I hope this book will prove valuable to those who are working in the fields of hematology and oncology.